2019
DOI: 10.1093/geroni/igz038.3056
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging a Self-Reliant Umbrella: Defining Successful Aging Among the Old-Old (80+) in Shanghai

Abstract: The Chinese old-old (80+) population has steadily increased in recent years; however, limited studies have examined how they age. The purpose of this study is to explore how the old-old in urban China define successful aging. Guided by grounded theory, community-dwelling old-old individuals participated in semi-structured, in-depth interviews (N= 97). Participants identified self-reliance as the goal of successful aging, which was supported by four proactive behaviors, including physical activity, financial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…Maintaining independence is a major factor in healthy aging for older adults in a variety of locations around the world. For example, research among Chinese older adults demonstrated that self-reliance was the overall goal of healthy aging, with emphasis on the concepts of physical activity, financial security, community connectedness, and willing acceptance of the declines brought about by aging (Chen et al, 2020). Although some of these concepts arose in Anchorage, our sample was unique because research participants were much less focused on self-reliance and instead focused on psychosocial factors of healthy aging.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining independence is a major factor in healthy aging for older adults in a variety of locations around the world. For example, research among Chinese older adults demonstrated that self-reliance was the overall goal of healthy aging, with emphasis on the concepts of physical activity, financial security, community connectedness, and willing acceptance of the declines brought about by aging (Chen et al, 2020). Although some of these concepts arose in Anchorage, our sample was unique because research participants were much less focused on self-reliance and instead focused on psychosocial factors of healthy aging.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance is understood as 'the mental recognition that personal circumstances change over time, and that one has accepted and come to terms with these changes' (Tate et al, 2013). The importance of accepting the realities of ageing was noted (Dionigi et al, 2011;Collis and Waterfield, 2015;Chen et al, 2019). This includes accepting the pain and physical limitations that come with age (Horder et al, 2013;Tate et al, 2013;Collis and Waterfield, 2015;Sato-Komata et al, 2015;Carr and Weir, 2017), as well as cognitive declines (Sato-Komata et al, 2015).…”
Section: Theme 1: Acceptancementioning
confidence: 99%
“…Eight studies included the theme of financial resources. Financial resources were needed to buy essentials (Bowling, 2006;Bassett et al, 2007;Torres and Hammarstrom, 2009;Horder et al, 2013;Nosraty et al, 2015;Sato-Komata et al, 2015;Chen et al, 2019), pay bills (Bowling, 2006;Horder et al, 2013) and retain autonomy in financial decisions (Nosraty et al, 2015;Chen et al, 2019) -'Money doesn't buy happiness, but it helps to buy the support you need to live well' (Bassett et al, 2007, p. 122). Financial resources were discussed in the context of having a sufficient pension, as stated by a Finnish female: 'Well, health of course and then sufficient income.…”
Section: Theme 5: Financial Resourcesmentioning
confidence: 99%
See 2 more Smart Citations